Knowledge, religiosity, and decision to use Sharia hospital services among residents in Central Java, Indonesia - Wilda, Amelia; Putri, Sabrina Mutiara; Vinalisa, Bintang Ananda Afrilianti; Salsabila, Reefa Dyah; Nafisatussalimah, Putri Sirry; Santoso, Arifin; Sulistyaningrum, Indriyati Hadi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2024)
The increasing tendency of society to apply Sharia principles in all aspects of life today is supported by the presence of Sharia hospitals that integrate Sharia values in administration, healthcare services, and patient care standards as regulated in the fatwa of the National Sharia Council (Dewan Syariah Nasional) No. 107/DSN-MUI/X/2016. Knowledge refers to everything known by an individual that can affect behavior. Meanwhile, religiosity is an individual's level of religious commitment that reflects the extent of belief in the values and expectations of the religion they adhere to or practice; in this study, it is the Muslim community. This research aims to examine the effect of the community's knowledge about Sharia hospitals and the religiosity of the Central Java community on their decision to seek medical treatment at Sharia hospitals. The research method used in this study was analytical observational with a cross-sectional study approach. Data was collected through direct questionnaires from the Central Java community using the snowball sampling technique. The research results indicate that knowledge and religiosity, both partially and simultaneously, affect the decision of the Central Java community to choose Sharia hospitals for medical treatment, with a p-value of 0,000. Partially, it is found that knowledge has an effect of 10,2%, while religiosity has an effect of 23% on the community's decision to seek medical treatment at Sharia hospitals. The conclusion of this study suggests that knowledge and religiosity significantly impact the Central Java community's decision to opt for Sharia hospitals for medical treatment.